Claim of Transport Commission Agent Liability and Compensation Provisions - Battah, Mohammad (Journal of Social Sciences (COES&RJ-JSS), 2020)
Through examining the transport commission agent liability, it is clear to us the heavy burden of transport commission agent liability. The legal nature of the transport commission agent commitment is the nature of commitment to achieving a result. The liability claim in the transport commission agency contract has two types, first, a claim in which the assignor or consignee demands compensation for damages and secondly, a claim in which the transport commission agent demands compensation to be paid by the person who causes damage. Therefore, the assignor and transporter shall return directly to each other to claim the rights of the transport contract. The passenger or consignee and transporter shall return directly to each other to claim the mentioned rights. In all cases, the transport commission agent shall be implicated in the claim. Since the legislator has prevented the agent of the transfer commission from establishing any conditions exempting him from liability in cases of loss and damage, he is obliged to compensate his client for full damages, except for the cases where the agent requires the transfer commission to determine his liability within the limits permitted by law, and we will know the provisions of compensation whether the compensation agreement or judicial compensation. Eventually, the prevailing trade development as well as the profession of transport commission agency, its importance and resulting legal disputes and problems led to carry out this study to identify the transport commission agent liability and its limits. In this study, we also deal with applying this liability through liability claim, how to dismiss this claim, and finally how to calculate the compensation.